Pemikiran Kritis Sadeq Jalal Al-Azm: Rekonstruksi Materialisme Historis atas Budaya dan Agama Arab Pasca 1967 - Bagus Mahardika; Yoyo Yoyo (Indo Publishing, 2026)
The Naksa incident of June 5 1967 was an epistemic shock for the Arab world. The defeat of Israel that led to the loss of the Sinai, the Golan, and the West Bank not only destroyed the region, but also undermined collective faith in the Arab project of renewal, unity, and progress. In the midst of narratives that blame external factors or divine destiny, Sadeq Jalal al-Azm 1934–2016 comes with a sharp analysis based on historical materialism. This article examines the construction of al-Azm's thought through a qualitative literature study with primary sources: Self-Criticism after the Defeat 1968 and Critique of Religious Thought 1969. The results of the study show that al-Azm broke with the theological-fatalistic explanation for defeat and replaced it with a structural diagnosis. He highlighted cultural dogmatism, magic in understanding religion, and the failure of Nasser's revolution to reach the level of public consciousness. The nationalism-socialism project only changed the political-economic structure, but failed to overhaul the superstructure of thought. As a solution, al-Azm proposed Hukumah Madaniyyah or civil secularism as a prerequisite for democracy and sustainable progress. Different from Hassan Hanafi who built the